Purification, molecular cloning and characterization of fibroblast growth factor-1 in mouse submandibular gland - YABUMOTO, Masafumi; TAKADA, Kazuaki; FUJITA, Yoshinori; OSAKI, Kiyohiko; OKAMOTO, Tetsuji (Japanese Journal of Oral and Maxillofacial Surgery, 1994)
A number of biologically active polypeptides or factors have been isolated from or claimed to be present in the submandibular gland of the mouse. Among them nerve growth factor and epidermal growth factor are extensively studied growth factors that occur in the submandibular glands. Therefore, the mouse submandibular gland is regarded to be both an endocrine organ and an exocrine organ. On the other hand, we have previously shown that mouse submandibular gland-derived epithelial cells require fibroblast growth factor-1 (FGF-1) for their growth and maintain a diploid chromosome number in serumfree culture. In this study, we therefore investigated whether mouse submandibular glands contain FGF-1 activities and whether the levels of these activities are dependent on androgen. We purified a 16, 000 dalton protein which stimulates growth of human umbilical cord vein-derived endothelial cells (HUVEC) from mouse submandibular glands by using heparin-Sepharose affinity and C4 reverse phase chromatography. The purified molecule was identified as FGF-1 bases on its biological activities, affinity for heparin, and N-terminal amino-acidsequence. Furthemore, the concentrations of the factor in male or testosterone treated female mouse submandibular gland were about 25 times higher than those of female or castrated male submandibular glands. In addition, northern blot analysis of mouse submandibular gland mRNA revealed that 2.3 kb and 4.1 kb FGF-1 mRNAs were expressed in the glands of male mice older than 4 weeks but not in female mice These results suggest that FGF-1 may play important roles in growth, differentiation and development of mouse submandibular glands, . and may act as an endocrine hormone.